(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This study is devoted to the research of human resources as a main source of sustainable regional development in Latvia. It is focused on two key concepts of human capital and migration. The aim of the study is to explore return migration geographies by looking at young return migrants as a resource and preconditions for sustainable regional development essential to Latvia.Return migration to the regions of Latvia is examined by two main research questions. What are the most recent return migrant characteristics in Latvia? How does return migration of young Latvians translates into regional geographies of return migration?Drawing on most recent available statistical data we elaborate on the return migration trends in Latvia, look at particular geographies of return migrants to the regions of Latvia. Findings show that return migrants are working age accompanied with their offspring’s, majority not married and return from another European country to the capital and other largest cities and surrounding municipalities. Even more, only ethnicity and country of previous residence serve as return migration predictor.